Moroccan Minors and the Internal Frontiers of Undocumented Migration (Turin, Northern Italy, 2003-2009) - Rossi, Alice (Mediterranean Journal of Social Sciences, 2012)
Illegal migration to Turin (one of the biggest industrial centres of Northern Italy) is related to the masculine collective idealamong minors and young migrants from Khouribga (Chaouia-Ouardigha, Morocco). This contribution will assess the impact of Italianlegal protection’s system of undocumented minors and securitization policy on their lives. By a long process leading to ‘PacchettoSicurezza’ in 2009 (a set of legislative measures aimed at controlling migrant’s flows across Italian external/internal borders) illegalmigration has become a criminal offence, a sort of ‘moral death’ normalized by media and technocratic services. This legal exclusion hasbecome a social experience in migrant daily life. My ethnographic data were collected from 2003 to 2009 in the assistance centre forminor undocumented migrants, which in 2003 Turin municipality opened up in Porta Palazzo, an historical migration neighborhood withthe largest open market in Europe. Here, I worked as a social operator in a multidisciplinary team (socio-anthropological and ethnopsychiatric)and I met young Moroccan migrants, mostly under age, refuting Municipality dorms and living in occupied houses, garagesor illegally rented houses and prison as well. This allowed me to get acquainted with their suffered trajectories among differentinstitutions and with their strategies to counter the legal criteria fixing the status of both undocumented migrants and minors. It is byfollowing these subtleties and the ways they were manipulated by social workers and young migrants alike, that I will try to describe thesubjective and material frontiers and the associated marginalities in this border-town context.